(untitled) (World Bulletin of Social Sciences, 2023)
This article is about using ICT in a classroom which is as a tool for language learning has a lot more benefit. It gives stimulus to undertake the tasks that the students may otherwise avoid. In an ICT enabled language learning class, the students would conduct the activities on the computer software platform and they will not have any sorts of hesitations or inhibitions. It would make repetitive tasks more interesting and would have content which could be inmultimedia formats.